Pengaruh GCG, Pengendalian Internal, Whistleblowing terhadap Pencegahan Fraud dengan Moderasi Komite Audit - Muhammad Saddam Fahrezi; Slamet Wahyudi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
Financial statement fraud continues to pose a danger to the viability and integrity of businesses, underscoring the necessity of strong control systems to stop fraud. With the audit committee acting as a moderating variable, this study attempts to examine how the whistleblower system, internal control, and good corporate governance (GCG) affect the prevention of financial statement fraud. This study used a quantitative methodology using primary data gathered from 100 PT Pegadaian (Persero) employees via questionnaires. Convenience sampling was the method employed. Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0 was used to evaluate the data. The findings show that both effective company governance and the whistleblower system have a positive and significant impact on preventing financial statement fraud. On the other hand, the audit committee and internal control have little impact. The audit committee does not moderate the link between the whistleblower system and GCG on financial statement fraud prevention, according to the moderating study. It does, however, considerably lessen the unfavorable link between financial statement fraud prevention and internal control. This study adds to the body of knowledge on fraud prevention by showing that formal oversight mechanisms through audit committees are not as important in preventing financial statement fraud as the efficacy of whistleblowing systems and the application of sound corporate governance.